Lacunar versus non-lacunar infarcts: pathogenetic and prognostic differences. Issue 6 (June 1992) - Landi, G; Cella, E; Boccardi, E; Musicco, M
Abstract : To characterise the pathogenetic and prognostic features of lacunar infarcts, 88 patients with these infarcts were compared with 103 patients with non-lacunar infarcts. Potential cardioembolic sources were significantly more frequent among patients with non-lacunar infarcts (p = 0.0025). Although the prevalence of hypertension was higher among lacunar infarcts, this difference was not statistically significant. However, the distribution of hypertensive patients in the two groups of lacunar and non-lacunar infarcts was influenced by the presence or absence of cardioembolic sources: hypertension was significantly associated with the presence of cardioembolic sources among non-lacunar infarcts, whereas among lacunar infarcts it was significantly more frequent in patients without a cardioembolic source. This indicates that cardioembolism may exert a confounding effect by suppressing the relation between hypertension and lacunar infarcts. In a mean follow up period of 28.1 months, lacunar infarcts had a significantly lower incidence of stroke recurrence and of myocardial infarction (age-adjusted survival analysis: p = 0.0008); mortality from all causes was also lower in patients with lacunar infarct (age-adjusted survival analysis: 0.04 less than p less than 0.05). In a multivariate regression analysis, stroke subtype was an independent predictor of new major vascular events. These findings support the lacunar hypothesis and should be considered in the planning of epidemiological and therapeutic studies in patients with cerebral infarction.